Effects of Temperature on percentage of Strongyle type eggs change in goat feces - Chadathong , Sirirat; Chunchob , Supatra; Wongsawang, Witsanu (Journal of Mahanakorn Veterinary Medicine, 2025)
Abstract: This study aimed to evaluate the effects of room temperature, refrigeration temperature (4°C) and freezing temperature (-20°C) on the percentage change of strongyle type eggs in goat feces by counting the number of strongyle type eggs using the Modified Mc Master technique. Results found that goat feces stored at refrigeration temperature had a lower percentage change of strongyle type eggs than goat feces stored at room temperature and freezing temperature, respectively. After storing goat feces for 28 days, refrigeration temperature reduced the percentage change of strongyle type eggs by 71.83 percent, freezing temperature reduced the percentage change of strongyle type eggs by 98.38 percent, and room temperature reduced the percentage change of strongyle type eggs by 100 percent. In addition, it was found that the percentage change of strongyle type eggs in goat feces at refrigeration, freezing and room temperature were significantly different from the 7th day onwards. This finding may be used to preserve goat fecal samples in order to maintain the integrity of strongyle type eggs before laboratory analysis.